2013
DOI: 10.1523/jneurosci.0805-13.2013
|View full text |Cite
|
Sign up to set email alerts
|

Ascl1/Mash1 Promotes Brain Oligodendrogenesis during Myelination and Remyelination

Abstract: Oligodendrocytes are the myelin-forming cells of the CNS. They differentiate from oligodendrocyte precursor cells (OPCs) that are produced from progenitors throughout life but more actively during the neonatal period and in response to demyelinating insults. An accurate regulation of oligodendrogenesis is required to generate oligodendrocytes during these developmental or repair processes. We hypothesized that this regulation implicates transcription factors, which are expressed by OPCs and/or their progenitor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
127
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(140 citation statements)
references
References 61 publications
(69 reference statements)
13
127
0
Order By: Relevance
“…For example, in addition to its role in OL specification (see above), Ascl1 knockout mice display a substantial reduction in mature OLs (Sugimori et al 2008), suggesting an important role in differentiation. Consistent with this, conditional ablation of the Ascl1 gene in OPCs reduces OL differentiation, instead favoring symmetric division events resulting in two OPCs (Nakatani et al 2013). Nevertheless, the genes that Ascl1 targets that mediate this effect are yet to be determined, as are the case for the equally important Nkx2-2 (see above).…”
Section: Regulators Of Ol Maturation and Myelinationmentioning
confidence: 60%
See 1 more Smart Citation
“…For example, in addition to its role in OL specification (see above), Ascl1 knockout mice display a substantial reduction in mature OLs (Sugimori et al 2008), suggesting an important role in differentiation. Consistent with this, conditional ablation of the Ascl1 gene in OPCs reduces OL differentiation, instead favoring symmetric division events resulting in two OPCs (Nakatani et al 2013). Nevertheless, the genes that Ascl1 targets that mediate this effect are yet to be determined, as are the case for the equally important Nkx2-2 (see above).…”
Section: Regulators Of Ol Maturation and Myelinationmentioning
confidence: 60%
“…Ascl1 (also known as Mash1) appears to have a broad role in promoting specification to the OL lineage, as Ascl1 knockout mice display a severe reduction in the number of OPCs (Parras et al 2007; Sugimori et al 2008). At early ages, Ascl1 promotes OL specification at the expense of neurons (Petryniak et al 2007); at later ages, it promotes OL specification at the expense of generation of astrocytes (Nakatani et al 2013). Sox9 also promotes glial specification, including to the OL lineage, as generation of OPCs is substantially delayed in Sox9 conditional knockout embryos (Stolt et al 2003).…”
Section: Transcription Factors Mediating Specification To the Ol Lineagementioning
confidence: 99%
“…However, because the progenitor and neuronal pools are significantly altered in the Ascl1 mutant prior to gliogenesis as a result of its earlier role in neurogenesis (Torii et al, 1999;Helms et al, 2005;Mizuguchi et al, 2006;Wildner et al, 2006), a direct role for Ascl1 in the specification and differentiation of OPCs in the spinal cord has not been completely addressed. In the neonatal brain, however, conditional deletion of Ascl1 in SVZ stem/progenitor cells showed that Ascl1 is required for OPC specification, and OPCspecific deletion of Ascl1 resulted in an increase in proliferation and a decrease in differentiation of OPCs during remyelination (Nakatani et al, 2013). We have shown that oligodendrogenesis in the spinal cord is dramatically reduced in the WM of Ascl1 CKO mice (Fig.…”
Section: Ascl1 Is Required To Balance the Number Of Gm And Wm Astrocymentioning
confidence: 66%
“…The expression of the transcription factor Sox17 is increased in active WM MS lesions, where it promotes OPC cell cycle exit and differentiation (Moll et al, 2013; Sohn et al, 2006). Similarly, Ascl-1 expression is increased at the active border of MS lesions, and guides OPC differentiation (Nakatani et al, 2013). Interestingly, the retinoid X receptor γ (RXRγ), a member of the nuclear receptor superfamily that mediates signaling by 9-cis retinoic acid (a vitamin A derivative), has been shown to drive oligodendrocyte differentiation and myelin sheath formation by OPCs (Huang and Franklin, 2012; Huang et al, 2011a,b).…”
Section: Mechanisms Of Tissue Repair and Regenerationmentioning
confidence: 99%